ANALYSIS OF FINANCIAL DISTRESS USING THE ALTMAN Z-SCORE AND TAFFLER METHODS IN CEMENT SUBSECTOR MANUFACTURING COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE FOR THE PERIOD 2018-2021 - Anwar; Puspita K, Armita; Muh. Ichwan Musa; Romansyah Sahabuddin; Anwar Ramli (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2023)
This research aims todetermine the potential for Financial Distress in cement manufacturing companies listed on the Indonesia Stock Exchange for the 2018-2021 period. The equation model used is the Altman Z-Score and the Taffler model. The data collection technique used is the documentation method with quantitative descriptive research data types. The results of the study show that cement sub-sector manufacturing companies for the 2018-2021 period have varied analysis results depending on the type of model implementation used. Companies that are in a healthy condition (safe area) for the two equation models are INTP in 2018-2021, and SMBR in 2018 for the Altman Z-Score model, while the SMGR Taffler model in 2018 is in a healthy condition (safe area). SMGR 2018-2020, WSBP 2018-2019, WTON 2018, and SMBR for 2020-2021 is in a gray area position for the Altman Z-Score equation model. While in the taffler model, companies that are in a gray area position are SMGR in 2019-2021, SMCB 2019-2020, WSBP in 2021, and SMBR in 2018 and 2021. Meanwhile companies that are in a bankrupt position are SMGR in 2021, SMCB in 2018- 2021, 2019-2020 WSBP, 2019-2021 WTON and 2019 SMBR for the Altman Z-Score model. In the taffler model, bankrupt companies are 2018 and 2021 SMCB, 2020 WSBP, and 2019-2020 SMBR. 2019-2020 WSBP, 2019-2021 WTON and 2019 SMBR for the Altman Z-Score model. In the taffler model, bankrupt companies are 2018 and 2021 SMCB, 2020 WSBP, and 2019-2020 SMBR. 2019-2020 WSBP, 2019-2021 WTON and 2019 SMBR for the Altman Z-Score model. In the taffler model, bankrupt companies are 2018 and 2021 SMCB, 2020 WSBP, and 2019-2020 SMBR